A Scoping Review of Factors Affecting Women of Childbearing Age in the Early Detection of Cervical Cancer - Ismarwati,; Vilvijaya, Soetrisno; Vilvijaya, Mulyanto; Mulyani, Sri (International Journal of Psychosocial Rehabilitation, 2020)
Cervical cancer is a malignant disease, and a very significant cause of death in women, which is predominantly instigated by the human papilloma virus (HPV) infection. The World Health Organization (WHO) reported an incidence rate of 14 per 100,000 sufferers and 6.8 per 100,000 deaths worldwide. The high mortality rate is possibly reduced through a comprehensive approach, including prevention, early diagnosis, effective screening and participation in the treatment of cervical cancer early detection programs. Furthermore, early detection is known to be influenced by individual, structural and social factors. The purpose of this study, therefore, is to determine the factors that influence early detection of cervical cancer in fertile women. The method used consists of five stages, encompassing the identification of scoping review questions, with the PEOS framework, distinguishing relevant studies using inclusion and exclusion criteria, through databases (PubMed, EBSCO, ScienceDirect, Wiley) and grey literature, article selection using PRISMA flow charts and critical appraisal involves The Joanna Bringgs Institute (JBI), mapping data, compiling, summarizing and result reporting. Furthermore, the seven selected literature fall into the grade A category, and then three themes emerged as a result of scoping review. These include individual factors (knowledge, attitudes, behavior, psychological), factors based on the facility providers (costs, health workers), and social influences (family support, friends, culture, religion). Conclusion: There are 3 factors assumed to inspire WCA to perform cervical cancer screening, comprising of individual, structural and social factors.